Analysis of the Role of the Jada Bahrin Village Government in the Direct Cash Assistance (BLT) Program During the Covid-19 Pandemic - Karina Novalia; Ilham Putra Fenza; Megia Wulandari; Nizwan Zukhri (Garuda Prestasi Nusantara Consulting, 2022)
On March 11, 2020 who declared that covid-19 became a global pandemic, l ock down policy implementation caused the paralysis of almost all activities that are normally carried out normally. Regarding this, the government is trying to create solutions or policies to help the economy affected by Covid-19. One of them is the management of village funds. In managing the village fund, the government also carries out a policy of Direct Cash Assistance (BLT), village officials play an important role in implementing the cash direct assistance program in the village. The purpose of this study is to analyze the role of the government of Jada Bahrin Village, Merawang District, Bangka Regency in the Cash Direct Assistance program during the COVID-19 pandemic and to analyze the benchmark for the success of the distribution of Cash Direct Assistance by the Jada Bahrin Village government during the COVID-19 pandemic. This type of research is qualitative research with a descriptive type of research. From the results of the study, it was found that the role of the Jada Bahrin Village government in the Direct Cash Transfer (BLT) program can be seen from 3 indicators, namely the role of a regulator, dynamicator, and facilitator. Village officials have a very large role in the regulation or rules for the distribution of the Cash Direct Assistance (BLT) program so that it can be accepted by the community quickly and precisely. As a dynamicator in the Cash Direct Assistance (BLT) program, the Jada Bahrin Village Apparatus provides direction regarding the terms and conditions of prospective recipients of Cash Direct Assistance (BLT). And the role of the village government as a facilitator is to assist the community by creating training, education and improving the skills of the community, and also providing financial assistance for the community